A thermal spray surface-strengthened anti-corrosion mining chain
By using double-layer thermal spray coating structure and hydrogen removal treatment on the mining chain, the problem of stress corrosion in the harsh corrosion environment of the mining chain is solved, and the higher breakage load, elongation and corrosion resistance are achieved, extending the service life of the chain.
Patent Information
- Application Number
- CN202411629882.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
High-strength ring chains for mines are prone to stress corrosion under harsh corrosion environments, resulting in cracking or fracture. Existing anti-corrosion measures such as aluminum spray or coatings have low wear resistance, making it difficult to meet the requirements of the mine service environment.
A double-layer thermal spray coating structure is adopted. The bottom layer thermal spray coating is 100-300μm thick on both sides of the weld. The rest of the chain ring is accompanied by a surface thermal spray coating of 50-100μm thick. The bottom layer is an iron-based self-melting powder coating, and the surface layer is a nickel-chromium alloy coating. The density and corrosion resistance of the coating are improved through hydrogen removal and oxygen-enriched oxidation.
It significantly improves the breakage load and elongation of the mining chain, enhances the protection of harmful elements, extends the service life of the chain, and improves corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of mining equipment, and in particular to a thermal spray surface-reinforced anti-corrosion mining chain. Background Art
[0002] The high-strength endless chain for mining is an important transmission component of the scraper conveyor and transfer machine on the working face of the coal mine. It is the force-bearing part, key part and vulnerable part of the equipment. Its performance will directly affect the normal operation of the scraper conveyor and the progress of safe production in the coal mine. Therefore, in actual work, the endless chain must have good strength and toughness and excellent comprehensive mechanical properties. 23MnNiMoCr54 is a high-strength chain steel. On the basis of low-carbon steel, it adds alloy elements such as Mn, Ni, Mo, Cr, etc., and improves the strength, plasticity and toughness of the steel through solid solution strengthening, grain boundary strengthening and second phase particle strengthening of these elements. At the same time, the fatigue life of the chain is improved by controlling harmful elements S, P, etc. in the steel. The production process of the chain is: cutting-heating bending ring-welding-heat treatment-stretching-pairing-inspection, and the chain heat treatment adopts quenching + tempering.
[0003] The operating environment of mining chains is often a harsh corrosive environment. Mining chains made of 23MnNiMoCr54 are prone to stress corrosion, leading to cracking or even breakage in a corrosive environment where they are under axial tensile stress for a long time.
[0004] Common surface treatment measures for high-strength endless chains include shot blasting, zinc-containing organic coatings, hot-dip galvanizing, hot-spraying aluminum and other anti-corrosion coatings. For example, CN117512434A discloses a mining chain steel containing Fe and inevitable impurities, and also contains the following chemical elements in the following mass percentages: C: 0.18-0.28%, Si: 0.2-0.6%, Mn: 0.9-1.6%, Cr: 0.4-0.8%, Ni: 0.9-1.6%, Mo: 0.4-0.9%, Cu: 0.02-0.25%, Al: 0.01-0.04%, Nb: 0.004-0.02%, V: 0.01-0.2%, N: 0.004-0.012%. Correspondingly, the present invention also discloses a chain made of the above-mentioned mining chain steel and a corresponding manufacturing method, which specifically includes the following steps: (1) smelting and casting; (2) heating and rolling; (3) ring welding; (4) quenching heat treatment: the quenching heating temperature is 840-980°C, the holding time is 1-3h, and then water cooling; (5) pickling; (6) preheating: the preheating temperature is 380-450°C, and the preheating time is ≥0.5h; (7) hot-dip galvanizing; (8) cooling and passivation: the cooling water temperature during chain cooling is 20-60°C, and the chain coating surface passivation time is ≥2min. However, the wear resistance of aluminum spraying, coating and other methods is low, and it is difficult to meet the environmental requirements of mine service.
[0005] CN114657334B discloses an annealing process for a mining-use endless chain steel 23MnNiMoCr54 with both structure control and hardness control, using a continuous annealing furnace, which adopts zoned heating and is divided into 12 to 16 zones, namely, a heating section, a high-temperature soaking section, a low-temperature soaking section, and a slow cooling section. After annealing by the process of the present invention, the metallographic structure of the high-strength mining-use endless chain steel 23MnNiMoCr54 is transformed from bainite + martensite before annealing to granular bainite + tempered troostite + ferrite with a small amount of granular carbides, the carbide spheroidization rate is ≥65%, and the depth of the surface decarburization layer is <250μm; the structure is dense and the hardness is uniform; the 23MnNiMoCr54 round steel produced by the process of the present invention can meet the production and use requirements of high-strength mining endless chains after making endless chains, and the number of fatigue cycles of the endless chains is ≥30,000 times. However, it does not mention the improvement of the corrosion resistance of the 23MnNiMoCr54 chain. Summary of the invention
[0006] In order to solve the above problems, the present invention sprays thermal spray coatings of different thicknesses on different parts of the chain links according to the influence of the welding process on the grains and performance near the chain link weld area. At the same time, through the double-layer thermal spray coating structure, the adhesion of the thermal spray coating is improved, the breaking load of the mining chain is increased, the breaking elongation is guaranteed, the corrosion resistance of the mining chain is improved, and the service life of the mining chain is increased.
[0007] To achieve the above object, the technical solution of the present invention is:
[0008] A thermal spray surface-strengthened anti-corrosion mining chain is composed of mutually nested chain links, which are closed by welding. A weld exists at the weld closure. A thermal spray coating with a thickness of 100-300 μm is sprayed on both sides of the weld within a range of 3-8 mm from the weld, and a thermal spray coating with a thickness of 50-100 μm is attached to the rest of the chain link.
[0009] The chain link can be divided into four parts: weld, weld affected zone, fusion zone between weld affected zone and parent material, and parent material. It is known from practice that stress corrosion fracture of mining chain often occurs on both sides of the weld, that is, the fusion zone between weld affected zone and parent material. This is because the temperature rises suddenly and cools rapidly during welding, which can lead to grain refinement in the weld affected zone. This area can obtain better mechanical properties, but it will cause a sudden change in performance and lattice size (lattice stress) between the weld affected zone and the parent material fusion zone. Once harmful elements enter, such as H, S, Cl, etc., stress corrosion may occur in this area. This scheme believes that the fusion zone between the weld affected zone and the parent material is within the range of 3-8mm from the weld. The width of the weld affected zone is related to the material, welding process, flux, size of welded parts, etc. In experience, the single-side width of the weld influence zone of the mining chain is about 3-5mm (from the weld to the point where the lattice size suddenly changes), and the fusion zone between the weld influence zone and the parent material is from the direction of the parent material to the normal lattice structure of the parent material (about 8mm away from the weld), that is, the distance from the weld to more than 8mm can be considered to be completely the parent material area. This solution improves the protection against elements such as H, S, and Cl by thickening the thermal spray coating in the fusion zone between the weld influence zone and the parent material on both sides of the weld. For this reason, the spraying accuracy needs to be ensured during the actual thermal spraying operation. In addition, this solution strengthens the spraying in the fusion zone between the weld influence zone and the parent material to change the overall stress distribution state on the chain link surface, thereby offsetting the lattice stress, while the conventional uniform spraying method cannot offset the stress, and may even introduce stress due to different thermal shrinkage caused by different materials of each layer.
[0010] Preferably, the base material of the chain link is 23MnNiMoCr54; the thermal spray coating is a double-layer structure, including a bottom thermal spray coating and a surface thermal spray coating; the surface thermal spray coating is connected to the bottom thermal spray coating, and the bottom thermal spray coating is attached to the base material of the chain link.
[0011] Preferably, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating, a nickel-aluminum alloy coating, or a nickel-copper-aluminum alloy coating. This design is because the surface thermal spray coating has high strength and good corrosion resistance, which can increase the breaking load of the chain link; the bottom thermal spray coating has high toughness and can slow down crack expansion.
[0012] Preferably, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:0.5-1.
[0013] Nickel-chromium alloy, nickel-aluminum alloy or nickel-copper-aluminum alloy has good corrosion resistance and is preferably used as the thermal spraying raw material of this scheme. However, its bonding strength with the substrate 23MnNiMoCr54 is low. If nickel-chromium alloy, nickel-aluminum alloy or nickel-copper-aluminum alloy is directly thermally sprayed on the surface of 23MnNiMoCr54, the formed coating has good corrosion resistance, but the coating durability is poor and it is easy to fall off. Therefore, the present invention creatively selects iron-based self-fluxing powder as the raw material of the thermal spraying process, as the bottom thermal spray layer of the anti-corrosion mining chain, the iron-based self-fluxing powder can be Fe55, Fe50, Fe60, etc., which has a high bonding strength with 23MnNiMoCr54, and it itself has good corrosion resistance, and has a high bonding strength with nickel-chromium alloy, nickel-aluminum alloy or nickel-copper-aluminum alloy. The thickness of the surface thermal spray coating is slightly lower than that of the bottom thermal spray coating. This is in consideration of the cost and wear resistance of the mining chain. If the surface thickness is too large, although the corrosion resistance will be better, the cost will also increase. At the same time, the static friction relative to the bottom thermal spray coating is large under stress, which may cause delamination.
[0014] Preferably, the method for preparing the thermal spray surface-strengthened anti-corrosion mining chain is:
[0015] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0016] Step (2) The rough chain is obtained by surface grinding and ultrasonic cleaning of the pre-processed chain;
[0017] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0018] Step (4) The dehydrogenation chain is heated to 400-500°C and then subjected to a first thermal spraying process to obtain a bottom thermal spraying layer, then cooled to room temperature and then heated to 400-500°C for a second thermal spraying to obtain a surface thermal spraying layer, and finally kept at 500-600°C for 1-2 hours under oxygen-rich conditions to obtain a thermal spray surface-strengthened anti-corrosion mining chain.
[0019] Preferably, the rough chain surface roughness Rz obtained by the thermal surface grinding treatment in step (2) is 0.10-0.50 μm.
[0020] Preferably, the heat treatment process in step (3) is: heating to 850-900°C at a rate of 3-5°C / min, keeping warm for 5-10 min, then quenching in water, cooling to room temperature, heating to 420-480°C at a rate of 3-5°C / min, keeping warm for 5-10 min, and then cooling to room temperature in water.
[0021] Preferably, the chain hydrogen content of the dehydrogenated chain in step (3) is less than 1 ppm.
[0022] Preferably, the first thermal spraying in step (4) is flame thermal spraying or arc thermal spraying; and the second thermal spraying is plasma thermal spraying.
[0023] Preferably, in the oxygen-enriched condition of step (4), the oxygen concentration range is 20-25%.
[0024] The preferred thermal spray surface-strengthened anti-corrosion mining chain described in this scheme has a double-layer structure. During preparation, 23MnNiMoCr54 rods are prepared into primary processing chains by ordinary processes for standby use. The traditional preparation method performs heat treatment after the primary processing chain is obtained to obtain a finished product. In the present invention, the primary processing chain is frosted. This is to remove oxide scale, surface impurities, oil stains, etc., and more importantly, to improve the adhesion of the underlying thermal spray coating. The frosting treatment can be achieved by sandblasting technology, and the sandblasting particle size is JIS-400. The surface must be cleaned after the frosting treatment, otherwise particulate slag will be formed between the underlying thermal spray coating and the substrate, affecting the strength of the underlying thermal spray coating.
[0025] It should be noted that in the continuous production process, the spatial positions that the chain link welds need to pass through are basically the same, which can ensure that the thermal spray coating with a thickness of 100-300μm is sprayed on both sides of the weld within 3-8mm range from the weld, and the rest of the chain link is covered with a thermal spray coating structure with a thickness of 50-100μm. If it is impossible to ensure that the spatial positions that the welds need to pass through are basically the same, an additional image recognition system and fixture are required to adjust the chain link position.
[0026] In order to ensure the performance of the thermal spray surface-strengthened anti-corrosion mining chain described in this scheme, after obtaining the rough chain, this scheme first performs heat treatment on it and performs hydrogen removal at the same time. Stress corrosion cracking is likely to be accompanied by hydrogen embrittlement, so the hydrogen atoms inside the 23MnNiMoCr54 rough chain must be removed before thermal spray coating.
[0027] The first thermal spraying in step (4) of this scheme uses flame or arc thermal spraying. This is because the iron-based self-fluxing powder has low melting point, good self-solubility and other properties, and can achieve thermal spraying without excessive energy. The second thermal spraying is plasma thermal spraying. The plasma thermal spraying particles have a high rate and can ensure the bonding strength between the surface thermal spraying layer and the bottom thermal spraying layer. Finally, the surface thermal spraying layer is kept at 500-600℃ for 1-2h under oxygen-rich conditions to form a dense oxide layer, achieve the effect of sealing holes, and prevent harmful elements such as H, S, and Cl from entering the anti-corrosion mining chain matrix strengthened by the thermal spraying surface. At the same time, this process also eliminates the stress of the thermal spraying coating, improves the lattice adaptability of the base material, the bottom thermal spraying layer, and the surface thermal spraying layer, and thus improves the strength of the coating.
[0028] Compared with the prior art, the present invention achieves the following beneficial effects:
[0029] 1. According to the stress corrosion fracture characteristics of mining chains, the present invention creatively proposes that on the same chain link, according to the influence of welding process on the grains and properties near the chain link weld zone, different thicknesses of thermal spray coatings are sprayed on different parts of the chain link, and the adhesion strength between the coating and the substrate is considered, and a double-layer thermal spray coating structure is designed. The surface thermal spray coating can increase the breaking load of the mining chain, and the bottom thermal spray coating has high toughness, can slow down crack expansion, and ensure the breaking elongation;
[0030] 2. The present invention fully considers the influence of the hydrogen content of the material itself on stress corrosion, performs dehydrogenation during the thermal spraying process, and performs oxygen-enriched oxidation after spraying, so that the density, wear resistance and corrosion resistance of the coating are improved, and at the same time, it has a higher breaking load and elongation. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0032] Embodiment 1: A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of nested chain links, which are closed by welding, with welds at the welded closures, and a 100 μm thick thermal spray coating is applied on both sides of the weld within a range of 3-8 mm from the weld, and a 50 μm thick thermal spray coating is applied to the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0033] Thermal spray surface-strengthened anti-corrosion mining chains are produced by the following process:
[0034] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0035] Step (2) Preliminary processing: the surface of the processed chain is subjected to frosting treatment and ultrasonic cleaning to obtain a rough chain;
[0036] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0037] Step (4) The dehydrogenation chain is heated to 500°C and then subjected to a first thermal spraying process by a flame thermal spraying process to obtain a bottom thermal spraying layer, then cooled to room temperature and then heated to 500°C and then subjected to a second thermal spraying process by plasma thermal spraying to obtain a surface thermal spraying layer, and finally kept at 600°C for 1 hour under oxygen-enriched conditions with an oxygen concentration of 22%, to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain.
[0038] Embodiment 2: A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of nested chain links, which are closed by welding, with welds at the welded closures, and a 300 μm thick thermal spray coating is applied on both sides of the weld within a range of 3-8 mm from the weld, and a 100 μm thick thermal spray coating is applied to the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0039] Thermal spray surface-strengthened anti-corrosion mining chains are produced by the following process:
[0040] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0041] Step (2) Preliminary processing: the surface of the processed chain is subjected to frosting treatment and ultrasonic cleaning to obtain a rough chain;
[0042] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0043] Step (4) The dehydrogenation chain is heated to 500°C and then subjected to a first thermal spraying process by a flame thermal spraying process to obtain a bottom thermal spraying layer, then cooled to room temperature and then heated to 500°C and then subjected to a second thermal spraying process by plasma thermal spraying to obtain a surface thermal spraying layer, and finally kept at 600°C for 1 hour under oxygen-enriched conditions with an oxygen concentration of 22%, to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain.
[0044] Embodiment 3: A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of nested chain links, which are closed by welding, with welds at the welded closures, and a 200 μm thick thermal spray coating is applied on both sides of the weld within a range of 3-8 mm from the weld, and a 75 μm thick thermal spray coating is applied to the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0045] Thermal spray surface-strengthened anti-corrosion mining chains are produced by the following process:
[0046] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0047] Step (2) Preliminary processing: the surface of the processed chain is subjected to frosting treatment and ultrasonic cleaning to obtain a rough chain;
[0048] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0049] Step (4) The dehydrogenation chain is heated to 500°C and then subjected to a first thermal spraying process by a flame thermal spraying process to obtain a bottom thermal spraying layer, then cooled to room temperature and then heated to 500°C and then subjected to a second thermal spraying process by plasma thermal spraying to obtain a surface thermal spraying layer, and finally kept at 600°C for 1 hour under oxygen-enriched conditions with an oxygen concentration of 22%, to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain.
[0050] Embodiment 4: A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of nested chain links, which are closed by welding, with welds at the welded closures, and a 200 μm thick thermal spray coating is applied on both sides of the weld within a range of 3-8 mm from the weld, and a 75 μm thick thermal spray coating is applied to the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:0.5, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0051] Thermal spray surface-strengthened anti-corrosion mining chains are produced by the following process:
[0052] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0053] Step (2) Preliminary processing: the surface of the processed chain is subjected to frosting treatment and ultrasonic cleaning to obtain a rough chain;
[0054] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0055] Step (4) The dehydrogenation chain is heated to 500°C and then subjected to a first thermal spraying process by a flame thermal spraying process to obtain a bottom thermal spraying layer, then cooled to room temperature and then heated to 500°C and then subjected to a second thermal spraying process by plasma thermal spraying to obtain a surface thermal spraying layer, and finally kept at 600°C for 1 hour under oxygen-enriched conditions with an oxygen concentration of 22%, to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain.
[0056] Embodiment 5: A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of nested chain links, which are closed by welding, with welds at the welded closures, and a 200 μm thick thermal spray coating is applied on both sides of the weld within a range of 3-8 mm from the weld, and a 75 μm thick thermal spray coating is applied to the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:0.5, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0057] Thermal spray surface-strengthened anti-corrosion mining chains are produced by the following process:
[0058] Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes;
[0059] Step (2) Preliminary processing: the surface of the processed chain is subjected to frosting treatment and ultrasonic cleaning to obtain a rough chain;
[0060] Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain;
[0061] Step (4) The dehydrogenation chain is heated to 500°C and then subjected to a first thermal spraying process by a flame thermal spraying process to obtain a bottom thermal spraying layer, and then cooled to room temperature and then heated to 500°C and then subjected to a second thermal spraying process by plasma thermal spraying to obtain a surface thermal spraying layer, and finally kept at 500°C for 1 hour under oxygen-enriched conditions with an oxygen concentration of 22%, to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain.
[0062] Comparative Example 1: The difference from Example 1 is that the mining chain is provided with a thermal spray coating with uniform thickness and double-layer structure, the thickness of which is 300 μm, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0063] Comparative Example 2: The difference from Example 1 is that the mining chain is provided with a thermal spray coating with uniform thickness and double-layer structure, the thickness of which is 100 μm, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0064] Comparative Example 3: The difference from Example 1 is that the mining chain has only a single-layer thermal spraying structure, and the sprayed coating is an iron-based self-fluxing powder coating.
[0065] Comparative Example 4: The difference from Example 1 is that the mining chain has only a single-layer thermal spraying structure, and the sprayed coating is a nickel-chromium alloy coating.
[0066] Comparative Example 5: The difference from Example 1 is that the mining chain is not subjected to dehydrogenation treatment during the preparation process.
[0067] Comparative Example 6: The difference from Example 1 is that the mining chain is not subjected to heat preservation treatment under oxygen-rich conditions during the preparation process.
[0068] Comparative Example 7: The difference from Example 1 is that a 400 μm thick thermal spray coating is applied on both sides of the weld of the mining chain within a range of 3-8 mm from the weld, and a 150 μm thick thermal spray coating is applied on the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0069] Comparative Example 8: The difference from Example 1 is that a 50 μm thick thermal spray coating is applied on both sides of the weld of the mining chain within a range of 3-8 mm from the weld, and a 30 μm thick thermal spray coating is applied on the rest of the chain link; the chain link substrate is 23MnNiMoCr54, the thermal spray coating is a double-layer structure, the surface thermal spray coating is connected to the bottom thermal spray coating, the bottom thermal spray coating is attached to the substrate of the chain link, the thickness ratio of the bottom thermal spray coating to the surface thermal spray coating is 1:1, the bottom thermal spray coating is an iron-based self-fluxing powder coating, and the surface thermal spray coating is a nickel-chromium alloy coating.
[0070] Comparative Example 9: The difference from Example 1 is that no surface thermal spraying process is performed.
[0071] Performance Test:
[0072] The anti-corrosion mining chains with thermal spray surface reinforcement obtained in Examples 1-5 and Comparative Examples 1-8 are round chain links with design specifications of Class D, 10×40 mm, and need to pass the following performance index tests:
[0073] 1. Hydrogen charging: Two samples a and b with a length of 150 mm were selected from the above Examples 1-5 and Comparative Examples 1-8, and sample b was pretreated: the sample surface was carefully scrubbed with a saturated NaOH solution to remove the oil stains on the sample surface, and then the residual NaOH solution on the surface was removed, and then the sample was rinsed with alcohol and dried with a hair dryer; then the sample was vertically suspended and immersed in a saturated HCl solution with thiourea for 24 hours; after being taken out, it was rinsed with clean water to remove the residual HCl solution, and then rinsed with alcohol, and then dried with a hair dryer;
[0074] 2. Test the breaking load with reference to GB / T 12718-2009 High Strength Round Link Chain for Mining, the results are shown in Table 1;
[0075] 3. This scheme judges the bonding strength of the thermal spray coating by the state of the thermal spray coating on the surface of the necking section when broken, which is divided into five levels: Level 0 means that there is no obvious crack on the surface of the necking section under a 100x stereo microscope; Level 1 means that a small amount of cracks can be seen on the surface of the necking section under a 100x stereo microscope, and there is no obvious crack on the surface of the necking section under a 10x stereo microscope; Level 2 means that a small amount of cracks can be seen on the surface of the necking section under a 10x stereo microscope, and there are no obvious cracks to the naked eye; Level 3 means that a small amount of cracks can be seen on the surface of the necking section with the naked eye, but the coating has not fallen off; Level 4 means that the coating on the surface of the necking section can be seen to fall off with the naked eye.
[0076] Table 1
[0077]
[0078] As can be seen from the above table, all samples of Examples 1-5 and Comparative Examples 1-8 of this scheme can meet the requirements of breaking load and elongation, while the strength of Comparative Example 9, which has not been strengthened by surface thermal spraying, is greatly reduced after pickling, indicating that thermal spraying can improve the corrosion resistance of mining chains. The detection means of this scheme is only a laboratory design condition, and actual use needs to consider timeliness and long-term service conditions. This scheme believes that Comparative Examples 1-8 have the following problems.
[0079] The difference between Comparative Example 1-2 and Example 1 is that Comparative Example 1-2 is a double-layer thermal spray coating of uniform thickness. It can be seen from the results that the thermal spray coating of Comparative Example 1 is thick enough. Although the breaking load and corrosion resistance are enhanced, the lattice stress in the weld influence zone is not offset, so the fracture still occurs at this position, so that the breaking elongation remains at the original level or even lower. At the same time, the spraying area of Comparative Example 1 is much larger than that of Example 1, and the cost is higher. The coating thickness of Comparative Example 2 is insufficient. After pickling, H atoms enter the substrate, resulting in reduced strength and elongation.
[0080] Comparative Example 3 is only a single-layer structure with poor corrosion resistance; Comparative Example 4 has insufficient bonding strength with the substrate, and a small amount of cracks can be seen on the surface of the necking section with the naked eye, and it is likely to fall off under long-term service conditions; Comparative Example 6 has not been subjected to oxygen-enriched insulation treatment, the gaps are not completely closed, and the breakage phenomenon is somewhat similar to that of Comparative Example 3.
[0081] Comparative Example 5 shows a chain that has not been treated for hydrogen removal. The results show that the breaking load of sample a is smaller than that of the other samples even without pickling.
[0082] Although the sample of comparative example 7 has a better breaking load, since the thermal spray coating thickness of 400μm is attached to the weld seam of the mining chain within 3-8mm range on both sides of the weld seam, the expansion rate is relatively large after the crack is generated, resulting in a decrease in elongation; the thermal spray coating thickness of comparative example 8 is relatively small and cannot provide a good anti-corrosion effect.
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A thermal spray surface-strengthened anti-corrosion mining chain, which is composed of chain links nested in each other, the chain links are closed by welding, and there is a weld at the welded closure, characterized in that: A thermal spray coating with a thickness of 100-300 μm is sprayed on both sides of the weld within a range of 3-8 mm from the weld, and a thermal spray coating with a thickness of 50-100 μm is attached to the rest of the chain link; The base material of the chain link is 23MnNiMoCr54; the thermal spray coating is a double-layer structure, including a bottom thermal spray coating and a surface thermal spray coating; the bottom thermal spray coating is an iron-based self-fluxing powder coating; the surface thermal spray coating is a nickel-chromium alloy coating, a nickel-aluminum alloy coating or a nickel-copper-aluminum alloy coating; The preparation method of the thermal spray coating is: Step (1) preparing the 23MnNiMoCr54 rod into a primary processing chain by heating, bending and welding processes; Step (2) The rough chain is obtained by surface grinding and ultrasonic cleaning of the pre-processed chain; Step (3) The rough chain is subjected to heat treatment and dehydrogenation treatment to obtain a dehydrogenated chain; Step (4) rotating the chain link, heating the dehydrogenation chain to 400-500° C., and then performing a first thermal spraying process to obtain a bottom thermal spraying layer, then cooling to room temperature and then heating to 400-500° C. to perform a second thermal spraying process to obtain a surface thermal spraying layer, and finally keeping the temperature at 500-600° C. for 1-2 hours under oxygen-rich conditions to obtain a thermally sprayed surface-strengthened anti-corrosion mining chain; the first thermal spraying is flame thermal spraying or arc thermal spraying; the second thermal spraying is plasma thermal spraying; and in the oxygen-rich conditions, the oxygen concentration ranges from 20 to 25%.
2. The anti-corrosion mining chain according to claim 1, characterized in that: The thickness ratio of the bottom thermal spray layer to the surface thermal spray layer is 1:0.5-1.
3. The anti-corrosion mining chain according to claim 1, characterized in that: The rough chain surface roughness Rz obtained by the surface frosting treatment in step (2) is 0.10-0.50 μm.
4. The anti-corrosion mining chain according to claim 1, characterized in that: The heat treatment process of step (3) is as follows: heating to 850-900°C at a rate of 3-5°C / min, keeping the temperature for 5-10 minutes, then quenching in water, cooling to room temperature, heating to 420-480°C at a rate of 3-5°C / min, keeping the temperature for 5-10 minutes, and then cooling to room temperature in water.
5. The anti-corrosion mining chain according to claim 1, characterized in that: The chain hydrogen content of the dehydrogenation in step (3) is less than 1 ppm.
Citation Information
Patent Citations
Mining chain steel, chain and manufacturing method thereof
CN117512434A
Cathode protection method for metal coating layer in weld zone of offshore structural steel
CN106435600A